ДОБОВА ОПТИМІЗАЦІЯ ГРАФІКУ РОБОТИ ГІДРОЕЛЕКТРОСТАНЦІЇ НА РИНКУ «НА ДОБУ НАПЕРЕД» - Є.В. Парус; І.В. Блінов; Д.О. Олефір (Праці Інституту електродинаміки Національної академії наук України, 2023)
A mathematical model of the daily optimization of available hydro resources of hydropower plants is presented as a tool for solving the problem of determining hourly volumes of electricity sales in the «day ahead» market segment, taking into account technological limitations and volumes of electricity under already concluded agreements. The method of preparation of input data in the part of calculations of the coefficients of the objective function and the system of constraints is presented. An example of solving the problem of daily optimization of the available hydro resources of the Kyiv HPP is demonstrated and the need to use additional non-price optimization criteria is substantiated. Bibl. 7, figure.